Postcards. - Alÿs, Francis. (Tufts University. Tisch Library., 2017)
Postcards in the set detail Alÿs' artistic endeavors, including his walk across the disputed Israel/Paletine border with a dripping can of paint and pushing a melting block of ice through city streets. Thirty postcards are represented in an accordion folded book.